ANALISIS PRINSIP KURIKULUM PENDIDIKAN AGAMA ISLAM PADA MATA PELAJARAN AL-QUR’AN HADIS DI MTs PPTI TAMO - Ibrahim, Depri; Muh. Andri; Rohana; Muhammad Rivaldi; Zuhdiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Curriculum is a fundamental component in the provision of education because it serves as a guide for achieving learning objectives. In the context of Islamic Religious Education (PAI), curriculum functions not only as a means of transferring knowledge but also as an instrument for building students' character, morals, and spirituality. This study aims to analyze the implementation of Islamic Religious Education curriculum principles in the Qur'an-Hadith subject at MTs PPTI Tamo. The study uses a descriptive qualitative approach with document analysis and observation of learning implementation. The research focuses on the application of the principles of relevance, flexibility, continuity, efficiency, and effectiveness in Qur'an-Hadith learning. The results show that the principle of relevance is the most dominant, as the learning material is linked to students' real lives, particularly in the context of environmental preservation and the formation of Islamic character. The principles of flexibility, continuity, and efficiency have been applied fairly well through the adjustment of learning methods and the use of digital technology. The principle of effectiveness has not been optimally achieved due to limited learning time and differences in students' abilities to reach memorization targets. This study also found the integration of local Mandar community values in curriculum implementation, making learning more contextual and meaningful. These findings indicate that the implementation of the PAI curriculum at MTs PPTI Tamo has accommodated the needs of students and the local socio-cultural environment, although further pedagogical innovation is still needed to improve the effectiveness of achieving curriculum objectives.